Biomarkers detected in cord blood predict vaccine responses in young infants - Baloh, Carolyn H.; Venturi, Guglielmo M.; Fischer, Bernard M.; Sadder, Liane S.; Kim-Chang, Julie J.; Chan, Cliburn; De Paris, Kristina; Yin, Li; Aldrovandi, Grace M.; Goodenow, Maureen M.; Sleasman, John W. (Frontiers in Immunology, 2023)
Introduction Factors influencing vaccine immune priming in the first year of life involve both innate and adaptive immunity but there are gaps in understanding how these factors sustain vaccine antibody levels in healthy infants. The hypothesis was that bioprofiles associated with B cell survival best predict sustained vaccine IgG levels at one year. Methods Longitudinal study of plasma bioprofiles in 82 term, healthy infants, who received standard recommended immunizations in the United States, with changes in 15 plasma biomarker concentrations and B cell subsets associated with germinal center development monitored at birth, soon after completion of the initial vaccine series at 6 months, and prior to the 12-month vaccinations. Post vaccination antibody IgG levels to Bordetella pertussis, tetanus toxoid, and conjugated Haemophilus influenzae type B (HiB) were outcome measures. Results Using a least absolute shrinkage and selection operator (lasso) regression model, cord blood (CB) plasma IL-2, IL-17A, IL-31, and soluble CD14 (sCD14) were positively associated with pertussis IgG levels at 12 months, while CB plasma concentrations of APRIL and IL-33 were negatively associated. In contrast, CB concentrations of sCD14 and APRIL were positively associated with sustained tetanus IgG levels. A separate cross-sectional analysis of 18 mother/newborn pairs indicated that CB biomarkers were not due to transplacental transfer, but rather due to immune activation at the fetal/maternal interface. Elevated percentages of cord blood switched memory B cells were positively associated with 12-month HiB IgG levels. BAFF concentrations at 6 and 12 months were positively associated with pertussis and HiB IgG levels respectively. Discussion Sustained B cell immunity is highly influenced by early life immune dynamics beginning prior to birth. The findings provide important insights into how germinal center development shapes vaccine responses in healthy infants and provide a foundation for studies of conditions that impair infant immune development.